Degradome-focused RNA interference screens to identify proteases important for breast cancer cell growth - Hölzen, Lena; Syré, Kerstin; Mitschke, Jan; Brummer, Tilman; Miething, Cornelius; Reinheckel, Thomas (Frontiers in Oncology, 2022)
Proteases are known to promote or impair breast cancer progression and metastasis. However, while a small number of the 588 human and 672 murine protease genes have been extensively studied, others were neglected. For unbiased functional analysis of all genome-encoded proteases, i.e. the degradome, in breast cancer cell growth we applied an inducible RNA-interference library for protease-focused genetic screens. Importantly, these functional screens were performed in two phenotypically different murine breast cancer cell lines, including one stem cell-like cell line that showed phenotypic plasticity under changed nutrient and oxygen availability. Our unbiased genetic screens identified 252 protease genes involved in breast cancer cell growth that were further restricted to 100 hits by a selection process. Many of those hits were supported by literature but some proteases were novel in their functional link to breast cancer. Interestingly, we discovered that the environmental conditions influence the degree of breast cancer cell dependency on certain proteases. For example, breast cancer stem cell-like cells were less susceptible to depletion of several mitochondrial proteases in hypoxic conditions. From the 100 hits, 9 proteases were functionally validated in murine breast cancer cell lines using individual knockdown constructs, highlighting the high reliability of our screens. Specifically, we focused on mitochondrial processing peptidase (MPP) subunits alpha (Pmpca) and beta (Pmpcb) and discovered that MPP depletion led to a disadvantage in cell growth, which was linked to mitochondrial dysfunction.